KONSEPSI AGAMA ISLAM DALAM AL-QURAN - Ahmad Mujahid; Haeriyyah Haeriyyah (Al-Risalah, 2020)
The problem with the diversity of Muslims is a religion without essence. Religion without substance. Having religion without practicing religious law. Having religion with the practice of sharia but minus the essence of being religious. This issue is discussed using the maudhuiy interpretation approach. Starting from the verses that use the term al-Islam, whether followed by the term al-dien or not, it is found that Islam refers to two meanings and or two conceptions, namely Islam as a religious institution and Islam as the essence of teachings. True Muslims are religious, not only limited to adhering to Islam as a religious institution but actually grounding Islam as teaching, namely actualizing Islamic teachings universally and holistically in life and life.